FACIAL NERVE ANATOMY - Rashidov Muhsin Narzi o’g’li (TADQIQOTLAR, 2025)
ABSTRACT . Facial nerve monitoring has been increasingly routinely used as an intraoperative adjunctive method to help the head and neck surgeon to identify and  minimize  facial  nerve  injury  during  parotid  surgery.  The  goals,  current applications, recent technical advances, and limitations of the method are reviewed. A main focus of this chapter is a review of several prospective clinical trials that have been performed in recent years that have analyzed the benefit of electrophysiological nerve  monitoring  during  parotid  surgery.  It  has  been  demonstrated  that  nerve monitoring reduces the risk of early postoperative facial nerve dysfunction in primary surgery, but not in revision surgery. The effect is more pronounced in total than in superficial  parotidectomy.  Monitoring  is  associated  with  shorter  surgical  times  in primary  superficial  parotidectomy  compared  to  total  parotidectomy.  Facial  nerve stimulation at the completion of parotidectomy helps to prognosticate the facial nerve functional  outcome.  A  lower  postdissection  to  predissection  ratio  of  the  maximal response amplitude is associated with early postoperative facial dysfunction. Facial nerve monitoring also helps the surgeon to avoid facial nerve injury when the facial nerve is not exposed during parotid surgery, such as during extracapsular dissection of a parotid neoplasm or sentinel node biopsy.